San Luis Water Co. receipt, November 1, 1891 - San Luis Water Company:::::: (1891)
Receipt for payment by Ah Louis (spelled Luis in the document) to the San Luis Water Co., for October 1 to November 1, 1901. Details of the payment and water services are listed on the receipt, as well as the bill price of three dollars.